Natural Resistance in Teak Clones to Leaf Skeletonizer Eutectona machaeralis Walker: an Appraisal - Roychoudhury, N.; Jain, Avinash; Joshi, K. C.; Lal, R. B. (Indian Forester, 1997)
The present paper deals with research accomplishments on natural resistance in teak clones against its prime insect pest, E. machaeralis Walker (Lepidoptera : Pyralidae). It succinctly describes the importance of this insect pest, modern concept of host resistance mechanisms and necessity for identification of resistant genotypes in practical utilization. Much emphasis has been given on evaluation of resistant teak clones against leaf skeletonizer and the factors responsible for natural resistance in teak clones have been highlighted. Use of resistant teak clones may offer a viable long term solution to the leaf skeletonizer menace.